Zinc nanostructure: a short review on phytochemicals-mediated biogenic synthesis and its anti-inflammatory effects - Ragavan, Omilla; Abdullah, Muhammad Nazrul Hakim; Fong, Lai Yen; Lim, Vuanghao; Yong, Yoke Keong (Springer, 2024)
Chronic inflammation underpins many severe diseases, often requiring anti-inflammatory drugs that can have adverse effects. Medicinal herbs offer an alternative but suffer from poor solubility, limiting their efficacy. Nanotechnology, particularly zinc oxide nanoparticles (ZnO NPs), presents a promising solution to enhance the therapeutic potential of herbal compounds. This review examines the nature and benefits of ZnO NPs in drug delivery systems compared to other nanomaterials. It highlights the advantages of biogenic synthesis of ZnO NPs, detailing the eco-friendly formation mechanisms and common characterization methods. The anti-inflammatory effects of biosynthesized ZnO NPs over the last five years are comprehensively reviewed, with insights into their mechanisms of action. Additionally, the pharmacokinetic and toxicokinetic profiles of ZnO NPs are explored to understand their biokinetics post-drug release. In conclusion, biogenically synthesized ZnO NPs enhance the bioavailability of medicinal plant compounds, offering a compelling alternative for treating inflammatory conditions.